Treasure of Local Wisdom in Strengthening Conservation and Ecotourism: Case Study of Dawan Indigenous People in Timor Tengah Utara District - Smaracdus C. V. Lake; Ricky Avenzora; Harnios Arief (Media Konservasi, 2017)
In the history of evolution, in fact the people of Indonesian archipelago have known local wisdom in the social life order that brings its people to be wise in managing various elements of nature. The purpose of this research were: 1) to analyze the local wisdom of Dawan community in North Central Timor District (TTU); 2) to strengthen the existence of local wisdom in ensuring the conservation and ecotourism domains. The method used in this study was phenomenology, which was then analyzed using one score one criteria scoring system. In various criteria, the data show that the local wisdom of the Dawan community in TTU District is in good condition or is in a domain of ‘still known’ and ‘still entrenched’. In strengthening the local wisdom of the Dawan indigenous people, ideas that can be considered for implementation are: firstly, conducting Integrated Stakeholders Management including government, community groups, academicians, NGOs, or private parties; secondly, strengthening indigenous institutions and enhancing the capacity of indigenous peoples; and thirdly, strengthening local wisdom through ecotourism. Thus those are expected to be able to stimulate all elements of society in TTU district in upholding local wisdom to strengthen conservation and ecotourism domains. Keywords: conservation, Dawan indigenous peoples, ecotourism, local wisdom, North Central Timor District